GLOBAL ANALYTIC SOLUTIONS FOR THE NONLINEAR SCHRODINGER EQUATION - BIYAR, MAGZHAN; DA SILVA, DANIEL OLIVEIRA (arxiv, 2019)
We prove the existence of global analytic solutions to the nonlinear Schr¨odinger equation in one dimension for a certain type of analytic initial data in L2
Keywords: Nonlinear Schrodinger Equation